Empowering language learners through children's literature - Mohd Azrul, Mohd Ezamir Azral (CENTRE FOR LANGUAGES AND PRE-UNIVERSITY ACADEMIC DEVELOPMENT, 2014)
This paper argues how from a meta-cognitive perspective, children's literature is able to empower English language learners in two areas: improving their literacy skills as well as increasing their awareness of the collective need to preserve the environment. Using eco-criticism as its theoretical framework, this research employs a meta-cognitive, close-reading analysis of K. S. Maniam's "Top Winner" and Iain Buchanan's "Fatimah's Kampung". The texts are found to employ nature and specific narrative styles in engaging and encouraging readers to read productively, and at the same time, critically assess their abilities to positively affect the environment in the 21st century.